Control Of Lipid Profile On Diabetes Mellitus Animal Models With Watercress And Black Rice Bran - Agustin Syamsianah; Herlisa Anggraini (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. Fluctuations of blood glucose levels in people with diabetes is a major cause of developing complications fromhyperglycemia ability to form the free radicals. Hyperglycemia condition that causes glucose autooxidation, proteinglycation, and polyol pathway activation so as to accelerate the formation of reactive oxygen compounds, furtherincreasing the modification of proteins, lipids, and DNA in various tissues. Various studies have been done, but theyrarely take advantage of local foodstuffs as a functional food therapy. Raw foods contain a powerful antioxidant that is acombination of watercress and black rice bran. This study aimed to analyze the effect of functional food supplements tochanges in the lipid profile of experimental animals . The results showed that levels of total cholesterol and triglyceridelevels decreased significantly after being given the supplement. There is a significant increase in HDL levels inexperimental animals after supplementation for 4 weeks, however, supplementation is not significant effect on LDLlevels decrease.